La ricerca nei 400 anni dell'Università degli Studi di Cagliari - Morelli, Micaela (UNICApress, 2021)
Research, along with teaching, has characterized since its birth, and continues to characterize, the life of Italian universities. This volume aims to retrace, through some of the most important researchers who have carried out their research in the University of Cagliari, the 400 years since its founding, to highlight the great vitality but also the difficulties it has gone through.